Contributions Sub Marine Tourism Opportunity To Work And Family Income Level Natal Sub-District Fishermen On The Beach Natal Mandailing Natal Regency Of North Sumatra Province - Muhammad Arfinsyah Nasution; Eni Yulinda; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conductedin the District of Natal Beach Natal Mandailing Natal regency of North Sumatra Provincein June 2013. Methods used to determine the respondents in this study is the census 30 people and proportional sampling of 27% of the total population.Tourism activities in Coastal Christmas brings a positive influence directly or indirectly to the family income of fishermen. The positive influence of perceived family fishermen are job opportunities for fishermen and fishing families. The amount of labor which is the owner or the owner's family members as much as 76 people or as many as 78.35% and the remaining 21 people, or 21.65% of the workers from the out side or not a family member.Keywords: Employment, Contribution Of Marine Tourism Subsector , Kecamatan Natal